Left ventricular chamber size predicts the race time of Japanese participants in a 100 km ultramarathon. Issue 4 (23rd March 2006) - Nagashima, J; Musha, H; Takada, H; Murayama, M
Abstract : Objective: As a subanalysis of an echocardiographic study performed on 291 Japanese participants in a 100 km ultramarathon, to estimate predictors of race time. Methods: A total of 247 male participants in a 100 km ultramarathon (age 20–73 years) were examined by echocardiography. Correlations between age, body surface area, monthly running distance, or echocardiographic variables and the race time were examined. Results: According to simple regression analysis, age ( r = 0.299, p<0.0001), monthly running distance ( r = −0.388, p<0.0001), left ventricular end diastolic diameter ( r = −0.300, p<0.0001), and left ventricular end systolic diameter ( r = −0.325, p<0.0001) correlated significantly with the race time. When multiple regression analysis was performed, age (f = 2.364), monthly running distance (f = −0.113), and left ventricular end systolic diameter (f = −2.361) remained significant predictors of the race time. Conclusion: Left ventricular diameter predicts the race time for a 100 km ultramarathon, in addition to age and amount of training.